2019
DOI: 10.1016/j.ijhcs.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the privacy risk awareness of teenagers in online social networks through soft-paternalism mechanisms

Abstract: Privacy Risk in Online Social Networks (OSNs) is one of the main concerns that has increased in the last few years. Even though social network applications provide mechanisms to control risk, teenagers are not often aware of the privacy risks of disclosing information in online social networks. The privacy decision-making process is complex and users often do not have full knowledge and enough time to evaluate all potential scenarios. They do not consider the audience that will have access to disclosed informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Finally, the participants considered for the experiments have a certain age distribution (approx. [12][13][14]. Therefore, these results cannot be extrapolated to users that are in other age range.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Finally, the participants considered for the experiments have a certain age distribution (approx. [12][13][14]. Therefore, these results cannot be extrapolated to users that are in other age range.…”
Section: Discussionmentioning
confidence: 96%
“…Schöning et al [222] tested significant differences by personalizing the styles of the nudges shown. Alemany et al [12] tested personalized nudges based on an estimation of the final audience before posting. In that work, the authors reported that teenagers used more restrictive policies when they were aware of the potential audience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations